Experimenting with varios styles to optimize the performance per crawl event - Colman, V.; Martens, J.; Soons, B.; Persyn, U. (Biomechanics and Medicine in Swimming X, 2006)
In this study, one disabled world record holder in crawl sprint is taken as a test case. In trying out various styles to optimize his performance, a rotating arm action style appeared to be the fastest on 50m sprint and a glide stroke with high elbow on longer distances. Movement analyses of the swimmer and observation of co loured water, displaced by the arm pull, were combined. During the downward movement of the hand in the stroke with high elbow, propulsion could be generated. In the two fastest styles, water appeared to be better displaced backward than in the other styles.